Analisis Persepsi Pelaku UMKM Terhadap Penerapan Laporan Keuangan Berbasis SAK EMKM Pada Usaha Pabrik Opak - Adila Sari; Annisa Khairani; Pricillia Deborah Valentine; Nayla Nurul Putri; Yulia Ribuna Br Bangun; Riska Franita (CV. ITTC INDONESIA, 2025)
This study aims to inform the perception of actors towards the implementation of financial statements based on SAK EMKM and to find the factors that influence it. One of the food processing MSMEs in Binjai City was the subject of the study, which was conducted using a qualitative phenomenological approach through in-depth interviews. The results show that MSME players realise how important financial recording is for the continuity of their business, but they still lack understanding and application of SAK EMKM. Factors such as education and business experience improve MSME players' perceptions of SAK EMKM, and the two main barriers to implementing SAK EMKM are lack of socialisation and time constraints. Based on the results of interviews with MSME business actors, opak factories do not yet have knowledge about the application of SAK EMKM-based financial reports, which aim to make it easier for MSME actors to calculate business financial reports properly and correctly.